Towards Estimating Entrainment Fraction for Dust Layers - Ural, Erdem A. (SpringerBriefs in Fire, 2011)
Towards Estimating Entrainment Fraction for Dust Layers closely examines the factors that can affect the assessment of a dust hazard, and outlines a new strawman method designed to help practitioners estimate the fraction of the dust accumulations that can become airborne. This book also aims to provide aid in the removal of aerodynamic disturbances of dust particles or agglomerates from layers or piles of cohesive and non-cohesive dusts. Towards Estimating Entrainment Fraction for Dust Layers is designed for practitioners as a reference guide for improving dust hazard assessment. Researchers working in a related field will also find the book valuable.